Effect of physical properties on the oscillation of an acoustically levitated droplet - Abbas Amoochi; Mohammad Reza Sheykholeslami; Rafat Mohammadi; Siamak Mazdak; Hamid Abdi (Journal of Particle Science and Technology, 2024)
Acoustic levitation is the only method capable of suspending samples with different material properties and geometries, even in the liquid phase. Despite its widespread applications, droplet levitation still has a problem controlling the droplet’s position due to initial oscillations before reaching stability. This research investigates the effects of droplet physical properties, such as viscosity, radius, and density, on droplet oscillation amplitude. For this purpose, numerical simulations that apply the effect of the mentioned properties with acceptable accuracy and precision results were conducted using COMSOL Multiphysics 6.1 commercial software. The unique feature of using a simulation is the ability to study the effect of each parameter independently from the rest of the properties, which is not directly possible in experimental tests. The results emphasize the direct influence of viscosity on droplet oscillation amplitude. They also demonstrated that elevated viscosity leads to a decrease in droplet oscillation amplitude. In addition, increasing the density because of the added weight decreases the droplet amplitude. The droplet radius effect is more complicated because it is associated with two opposite effects. Increased droplet radius has the same effect as viscosity because of weight addition. On the other hand, a larger droplet's radius enlarges the cross-section and leads to a weak increase in droplet amplitude.